Kontekstualisasi Pekabaran Injil dalam Budaya Aluk Todolo: Analisis Historis-Teologis terhadap Misi Zending Belanda di Tana Toraja - Atasia Irmansyah Dorman; Charisal B.S. Manu (Vieka Wahana Semesta, 2026)
This article examines the contextualisation of the Gospel within the Aluk Todolo tradition by conducting a historical and theological analysis of the Dutch Zending mission in Tana Toraja. The proclamation of the Gospel in the early 20th century did not occur in isolation, but rather encountered a system of beliefs and local culture that was already deeply ingrained in the lives of the Toraja people. Through a descriptive qualitative approach and a literature review, this study examines the characteristics of Aluk Todolo, the process of the Gospel’s introduction, and the missionary strategies adopted by the Gereformeerde Zendingsbond (GZB), particularly through the figure of Antonie Aris van de Loosdrecht. The research findings indicate that the proclamation of the Gospel was carried out in a contextual manner through the use of the local language, the translation of theological concepts such as ‘Puang Matua’, and educational and social methods that respected local cultural values. The interaction between the Gospel and Aluk Todolo created a dynamic that was not merely adversarial, but also dialogical and transformative. This adaptation allowed the Gospel to be accepted without entirely erasing the Toraja cultural identity. This study emphasises that a mission approach that is contextually appropriate and sensitive to local culture is vital in conveying the Gospel in a relevant and meaningful way within the community.